2004
DOI: 10.1002/cncr.20536
|View full text |Cite
|
Sign up to set email alerts
|

Value of routine follow‐up for patients cured of laryngeal carcinoma

Abstract: BACKGROUND Routine follow‐up offered to patients with laryngeal carcinoma in The Netherlands consisted of 22 routine visits over a time period of 10 years after treatment. The primary aims of the follow‐up were to detect cancer recurrence in asymptomatic patients and to achieve better survival outcome by reducing cancer‐specific mortality rates. METHODS A longitudinal cohort study was performed to evaluate the effect of this follow‐up schedule. Between January 1990 and January 1995, the authors studied all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 16 publications
3
80
1
5
Order By: Relevance
“…About 50%-70% of patients with head and neck squamous cell carcinoma (HNSCC) achieve a complete response, with residual or recurrent disease being detected in 30%-50% of cases either at the primary site or in the neck (6). Approximately 80% of tumor recurrence in HNSCC occurs during the first 2 y after treatment (7).…”
mentioning
confidence: 99%
“…About 50%-70% of patients with head and neck squamous cell carcinoma (HNSCC) achieve a complete response, with residual or recurrent disease being detected in 30%-50% of cases either at the primary site or in the neck (6). Approximately 80% of tumor recurrence in HNSCC occurs during the first 2 y after treatment (7).…”
mentioning
confidence: 99%
“…Laryngeal cancers account for approximately 2% of all cancers (2.3% in males and 0.4% in females) (1) . All of our 40 study patients were male, perhaps because more males than females smoke in our country.…”
Section: Discussionmentioning
confidence: 99%
“…11 in terms of all male cancers worldwide. The disease is most common in males aged 50-70 years and is rare in those aged <20 years (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into follow-up strategies for head-and-neck cancer has not shown an advantage in overall survival with routine cancer surveillance for timely detection of recurrence [5][6][7][8][9][10] , and no randomized clinical trials have compared follow-up strategies with no follow-up 11 . The literature pertaining to how follow-up care can most effectively manage morbidity and address other health needs in head-and-neck cancer patients is limited 12,13 .…”
Section: Introductionmentioning
confidence: 99%